Neutron shield material, method for manufacturing neutron shield material, and spent fuel aggregate storage container
The neutron shielding material, comprising hydrogenated bisphenol A diglycidyl ether, tetrahydrophthalic anhydride derivatives, and a specific curing accelerator, addresses the challenges of heat resistance, neutron shielding, and sealing performance, maintaining effective hydrogen density and moldability.
Patent Information
- Application Number
- JP2023180495
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-19
- Publication Date
- 2025-05-02
AI Technical Summary
Existing neutron shielding materials for spent fuel assemblies face challenges in achieving high heat resistance, neutron shielding performance, and sealing performance simultaneously, while also maintaining the hydrogen density and moldability required for effective radiation shielding.
A neutron shielding material composed of a cured product of a resin composition containing hydrogenated bisphenol A diglycidyl ether as the main agent, a curing agent selected from derivatives of tetrahydrophthalic anhydride, and a solid or semi-solid curing accelerator with a melting point between 30°C and 45°C, which is heated to ambient temperatures of 45°C to 55°C for curing.
The proposed solution achieves high glass transition temperatures, maintaining heat resistance and neutron shielding performance even after exposure to high temperatures for extended periods, while ensuring excellent moldability and storage properties of the curing accelerator.
Smart Images

Figure 2025070286000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a neutron shielding material containing an epoxy resin as a main component, a method for manufacturing the neutron shielding material, and a spent fuel assembly storage container equipped with the neutron shielding material. [Background technology]
[0002] Spent fuel assemblies removed from a nuclear reactor after nuclear power generation are cooled for a certain period in a cooling pool within the nuclear power plant, and then transported to a processing facility such as a fuel reprocessing plant or an intermediate storage facility. If the amount of spent nuclear fuel generated exceeds the reprocessing capacity, it will be necessary to store the spent nuclear fuel for a long period of time. Therefore, dry storage after wet storage in a cooling pool is being considered.
[0003] Dry casks made of metal are used for dry storage of spent nuclear fuel. Dry casks are containers that contain spent fuel assemblies, and are used to store spent nuclear fuel inside and outside nuclear power plants, and to transport spent nuclear fuel. In general, dry casks are made of carbon steel, low alloy steel, and synthetic resin neutron shielding materials, and are formed as multi-layered containers. Spent nuclear fuel releases decay heat, and dry casks remove this heat by dissipating it through natural convection.
[0004] Even after the nuclear fission reaction and radioactive decay have decayed to some extent in the cooling pool, spent nuclear fuel continues to emit high doses of neutrons and gamma rays as well as a large amount of decay heat. In addition, when high-burnup nuclear fuel with a high enrichment level is used, it is expected that the amount of heat generated by the spent nuclear fuel and the neutron intensity will increase. Therefore, casks that store spent fuel assemblies are required to have high neutron shielding performance, sealing performance, heat resistance, etc.
[0005] Conventionally, neutron shielding materials made of synthetic resins have been used as lightweight, solid neutron shielding materials. In general, synthetic resin neutron shielding materials contain neutron absorbing materials and flame retardants. Since high neutron shielding performance is required for synthetic resins, those containing a high density of hydrogen atoms, which have a large elastic scattering cross section for neutrons, are used.
[0006] In dry storage of spent nuclear fuel, a large amount of decay heat is released, and the thermal load on the synthetic resin used in the casks becomes an issue. Neutron shielding materials made of synthetic resins are required to have high heat resistance as well as high neutron shielding performance. In this case, the temperature of the neutron shielding material may rise to around 150°C. There is a trade-off between the hydrogen density and heat resistance of synthetic resins, and the higher the hydrogen density, the lower the heat resistance tends to be. Therefore, various studies have been conducted on synthetic resin neutron shielding materials to achieve both high hydrogen density and heat resistance.
[0007] Patent Document 1 states that the number of hydrogen atoms contained per unit volume is 4.5 × 10 22 ~5.6×10 22 pieces / cm 3 , the boron isotope contained per unit volume 10 The number of B atoms is 6×10 19 ~1.7×10 20 pieces / cm 3 The neutron shielding material is described as follows. The main components include bisphenol A type epoxy compounds, novolac type epoxy resins, various glycidyl ester type epoxy compounds, glycidyl amine type epoxy compounds, and biphenyl type epoxy compounds. The hardeners include aromatic amines, cyclic amines, polyamidoamine amine hardeners, acid anhydride hardeners, and imidazole hardening accelerators.
[0008] Patent Document 2 describes a composition for a neutron shielding material that contains a hydrogenated bisphenol type epoxy, a curing agent component having at least one or more ring structures and a plurality of amino groups, and a boron compound. Examples of the hydrogenated bisphenol type epoxy include hydrogenated bisphenol A type epoxy and hydrogenated bisphenol F type epoxy. As polymerization conditions, it is said that heating at 50°C to 200°C for 1 hour to 3 hours is preferable.
[0009] Neutron shielding materials made of synthetic resins require high moldability in order to ensure the ability to seal spent nuclear fuel. In order to shield against radiation emitted from spent fuel, it is important to mold the neutron shielding material that is installed to surround the spent fuel into the shape designed. Regarding the moldability of thermosetting resins, (1) the raw material liquid before hardening must flow into the mold without gaps, (2) there must be no sink marks when hardening, and no gaps between the edge and the installation location after hardening, and (3) no air bubbles or voids must remain inside after hardening.
[0010] However, since the synthetic resin used in the casks is required to have high heat resistance, it is difficult to ensure high moldability. There is a trade-off between the heat resistance and moldability of synthetic resins, and the higher the heat resistance, the lower the moldability tends to be. When the glass transition temperature of a synthetic resin increases, the heat resistance improves, but the fluidity decreases and the flow into the mold becomes poor. Therefore, it is necessary to suppress the viscosity of the raw material liquid that is the raw material for the neutron shielding material.
[0011] Patent Document 3 describes a neutron shielding material composed of a cured product obtained by adding a curing agent that causes ring-opening polymerization of epoxy groups to a base agent that contains at least one compound containing two epoxy groups in the molecule. Examples of base agents include bisphenol A type epoxy compounds, novolac type epoxy resins, alicyclic glycidyl ether type epoxy compounds, various glycidyl ester type epoxy compounds, glycidyl amine type epoxy compounds, and biphenyl type epoxy compounds. Examples of curing agents include amine-based curing agents such as aromatic amines, alicyclic amines, and polyamidoamines, acid anhydride-based curing agents, and imidazole-based curing accelerators. The blending ratio of each component is set so that the viscosity of the liquid mixture at 30°C to 100°C does not exceed 200 dPa·s.
[0012] In order to improve the heat resistance of synthetic resins, it is important to increase the crosslink density. It is known that the higher the curing temperature of a thermosetting resin, the higher the crosslink density and the higher the glass transition temperature. However, the higher the curing temperature, the faster the curing reaction, which can cause sink marks on the surface of the cured product and air bubbles and voids inside the cured product. Therefore, a technology has been proposed to cure the raw material liquid that is the raw material for neutron shielding materials at around room temperature.
[0013] Patent Document 4 describes a neutron shielding material made of a cured product obtained by adding 55% by weight or more of an acid anhydride curing agent and 2% by weight or more of a curing accelerator to 100% by weight of a base agent containing at least one compound containing two epoxy groups in the molecule, and reacting them at a temperature of 40°C or less. Examples of the base agent include bisphenol A type epoxy compounds, novolac type epoxy resins, alicyclic glycidyl ether type epoxy resins, various glycidyl ester type epoxy resins, and glycidyl amine type epoxy resins. Examples of the curing agent include maleic anhydride, phthalic anhydride, methylnadic anhydride, succinic anhydride, trimellitic anhydride, and chlorendic anhydride. Examples of the curing accelerator include imidazole compounds.
[0014] Patent Document 5 describes a neutron shielding material that is composed of a resin composition containing a flame retardant and an epoxy resin, the epoxy resin containing a unit skeleton derived from a hydrogenated epoxy base resin containing two or more epoxy groups in the molecule, and the flame retardant is contained in a ratio of 40% by mass to 60% by mass based on the resin composition. Examples of the curing agent include acid anhydrides, dicyandiamide, and phenolic resins. Examples of the curing accelerator include non-imidazole compounds. It is said that the curing temperature can be any of a low temperature range of 5°C to less than 50°C, a medium temperature range of 50°C to less than 80°C, and a high temperature range of 80°C to 200°C. [Prior art documents] [Patent documents]
[0015] [Patent Document 1] JP 2004-198281 A [Patent Document 2] JP 2003-050295 A [Patent Document 3] JP 2003-167091 A [Patent Document 4] JP 2007-033059 A [Patent Document 5] Patent Publication No. 2021-050972 Summary of the Invention [Problem to be solved by the invention]
[0016] There is a demand for technology that can achieve high levels of heat resistance, neutron shielding, and sealing performance for neutron shielding materials used in casks, which are storage containers for spent fuel assemblies. To improve neutron shielding performance, it is important to achieve high hydrogen density and high heat resistance. To improve sealing performance, it is also important to achieve high moldability and high crosslink density, i.e., glass transition temperature.
[0017] In Patent Document 1, the number of hydrogen atoms contained per unit volume of the neutron shielding material is ensured. However, the number of hydrogen atoms is ensured as a value at the initial stage of manufacture before hardening. When the neutron shielding material is used in a cask, depending on the temperature of the spent fuel and the storage period, hydrogen is released by an oxidative dehydrogenation reaction, and the number of atoms decreases. Therefore, it is desired to further improve the hydrogen density and neutron shielding performance of the neutron shielding material.
[0018] In Patent Document 2, polymerization conditions are assumed in which an amine-based curing agent is used and the material is heated at 50°C to 200°C for 1 to 3 hours. However, under such polymerization conditions, the curing speed may not be sufficiently slowed. When an amine-based curing agent is used, the curing reaction may progress in a short time due to the reactivity of primary amines and the catalytic action of tertiary amines. In such cases, bubbles and voids are likely to form inside the cured product, resulting in problems such as reduced neutron shielding performance and sealing performance.
[0019] In Patent Document 3, the composition is formulated so that the viscosity of the liquid mixture at 30°C to 100°C does not exceed 200 dPa·s. However, since the viscosity of the liquid mixture increases with decreasing temperature, even if it does not exceed 200 dPa·s at around 100°C, it may increase to 1000 to 5000 dPa·s or more at around room temperature. When the viscosity becomes so high, it becomes difficult for the gas caught in the liquid mixture to escape, and bubbles are easily formed inside the cured product, resulting in problems such as reduced neutron shielding performance and sealing performance.
[0020] In Patent Document 4, the base agent is cured at 40°C or less. However, at a low temperature of 40°C or less, it is not easy to uniformly proceed with the curing reaction. Since the rate of heat generation during curing varies, it is easy to form a non-uniform region in which cured and uncured regions are mixed during curing. In addition, when a curing accelerator that is solid at 40°C or less is used, the effect of promoting the curing reaction is not uniform, and non-uniform regions are easily formed. When cured and uncured regions are mixed, there are places that cannot follow the shrinkage of the volume during curing. Therefore, there is a problem that sink marks are generated on the surface of the cured product and voids are formed inside the cured product, resulting in reduced neutron shielding performance and sealing performance.
[0021] Some types of hardening accelerators are liquid at temperatures below 40°C. However, liquid hardening accelerators are prone to deterioration in air and have storage problems. When a liquid hardening accelerator is used, the hardening reaction does not proceed easily due to oxidative deterioration caused mainly by oxygen in the air during storage, and uneven areas in which hardened and unhardened areas are mixed tend to form. As mentioned above, when hardened and unhardened areas are mixed, there are areas that cannot keep up with the shrinkage of the volume during hardening. Therefore, there are problems such as sink marks on the surface of the hardened product and voids being formed inside the hardened product, which reduces the neutron shielding performance and sealing performance. Therefore, it is necessary to improve the storage stability of the hardening accelerator.
[0022] In Patent Document 5, a non-imidazole compound is used as a curing accelerator. However, the non-imidazole curing accelerator has a drawback that the reaction that generates radicals is slower than that of the imidazole curing accelerator. When a non-imidazole curing accelerator is used, the reaction rate of the crosslinking reaction is slow, and it is difficult to obtain a high crosslinking density, so that the glass transition temperature (Tg) is low and the heat resistance performance is low.
[0023] Therefore, the present invention aims to provide a neutron shielding material that is capable of achieving a balance between heat resistance performance, neutron shielding performance, and sealing performance at a higher level than conventional methods, and that also has excellent preservation properties for hardening accelerators, a manufacturing method for the neutron shielding material, and a spent fuel assembly storage container equipped with the neutron shielding material. [Means for solving the problem]
[0024] The heat resistance performance is determined by whether or not the material has a high glass transition temperature. The neutron shielding performance is determined by whether or not the material has a high hydrogen density, and further, whether or not hydrogen is not released by an oxidation-dehydrogenation reaction even during heat load due to the high temperature of spent fuel or during long-term storage. The sealing performance is determined by whether or not the material has high moldability. The moldability means that (1) the raw material liquid before hardening flows into the mold without gaps, (2) there is no sink mark during hardening, and there is no gap between the end and the installation location after hardening, and (3) there are no bubbles or voids remaining inside after hardening. The storage stability is determined by whether or not the hardening accelerator is solid during storage. Therefore, the neutron shielding material according to the present invention has a high glass transition temperature and a high hydrogen density, and this hydrogen density does not decrease even under long-term heat load. In addition, high moldability, i.e., the raw material liquid has high fluidity, and after hardening, there are no gaps at the end or the like, no bubbles or voids remain inside, and the hardening accelerator is solid or semi-solid at room temperature.
[0025] Specifically, in order to solve the above-mentioned problems, the neutron shielding material according to the present invention is a neutron shielding material whose main component is an epoxy resin, and is composed of a cured product of a resin composition including a base agent containing a compound containing two epoxy groups in the molecule, a curing agent that causes ring-opening polymerization of the epoxy groups, a curing accelerator that accelerates the curing reaction of the base agent and the curing agent, a flame retardant, and a neutron absorbing material, wherein the base agent is hydrogenated bisphenol A diglycidyl ether, the curing agent is two or more selected from the group consisting of 4-alkylendomethylenetetrahydrophthalic anhydride, 7-alkylendomethylenetetrahydrophthalic anhydride, and endomethylenealkyltetrahydrophthalic anhydride, and the curing accelerator is a compound that is solid or semi-solid at room temperature and has a melting point of 30°C or more and 45°C or less.
[0026] The method for producing a neutron shielding material according to the present invention is a method for producing a neutron shielding material mainly composed of an epoxy resin, the neutron shielding material being composed of a cured product of a resin composition including a base agent including a compound containing two epoxy groups in a molecule, a curing agent which causes ring-opening polymerization of the epoxy groups, a curing accelerator which accelerates a curing reaction between the base agent and the curing agent, a flame retardant, and a neutron absorbing material, the base agent being hydrogenated bisphenol A diglycidyl ether, the curing agent being 4-alkyl-end methylene tetrahydrophthalic anhydride, 7-alkyl-end methylene tetrahydrophthalic anhydride, and ... The curing accelerator is a compound having a melting point of 30°C or more and being solid or semi-solid at room temperature, and the curing accelerator is heated and melted at an ambient temperature of 45°C or more and 55°C or less to prepare a raw material liquid in which the base agent, the curing agent, the curing accelerator, the flame retardant and the neutron absorbing material are mixed, and the raw material liquid is thermally cured at an ambient temperature of room temperature or more and 55°C or less to obtain the cured product.
[0027] Further, a spent fuel assembly storage container according to the present invention is a spent fuel assembly storage container for storing spent fuel assemblies, the spent fuel assembly storage container comprising an outer container, an inner container disposed inside the outer container, a basket disposed inside the inner container and for accommodating spent fuel assemblies, and a neutron shielding material disposed between the outer container and the inner container, the neutron shielding material being composed of a base material containing a compound having two epoxy groups in a molecule, a curing agent which causes ring-opening polymerization of the epoxy groups, and a neutron shielding material which causes ring-opening polymerization of the base material and the curing agent. The curing agent is composed of a cured product of a resin composition containing a curing accelerator that accelerates a curing reaction by a curing agent, a flame retardant, and a neutron absorbing material, the main agent being hydrogenated bisphenol A diglycidyl ether, the curing agent being two or more selected from the group consisting of 4-alkyl endomethylene tetrahydrophthalic anhydride, 7-alkyl endomethylene tetrahydrophthalic anhydride, and endomethylene alkyl tetrahydrophthalic anhydride, and the curing accelerator is a compound that is solid or semi-solid at room temperature and has a melting point of 30°C or higher and 45°C or lower. Effect of the Invention
[0028] According to the present invention, it is possible to provide a neutron shielding material which is capable of achieving a balance between heat resistance performance, neutron shielding performance, and sealing performance at a higher level than conventionally possible, and which also has excellent preservation properties for the hardening accelerator, a manufacturing method for the neutron shielding material, and a spent fuel assembly storage container equipped with a neutron shielding material. [Brief description of the drawings]
[0029] [Figure 1] FIG. 1 is a perspective view showing an example of a spent fuel assembly storage container according to an embodiment of the present invention. [Diagram 2] 1A to 1C are diagrams showing a method for manufacturing a neutron shielding material according to an embodiment of the present invention. [Diagram 3] FIG. 13 is a diagram showing the relationship between the set temperature and the maximum temperature when heating and mixing a raw material liquid obtained by mixing raw materials for a neutron shielding material. [Figure 4] FIG. 13 is a diagram showing the relationship between the set temperature and the curing time when heating and mixing a raw material liquid obtained by mixing raw materials of a neutron shielding material. [Figure 5A] FIG. 2 is a graph showing the relationship between the amount of a hardener, which is a raw material of a neutron shielding material, and the glass transition temperature. [Figure 5B] FIG. 2 is a graph showing the relationship between the amount of a hardening accelerator, which is a raw material of a neutron shielding material, and the glass transition temperature. [Figure 5C] FIG. 2 is a graph showing the relationship between the amount of neutron absorbing material, which is a raw material of a neutron shielding material, and the glass transition temperature. [Figure 6A] FIG. 2 is a graph showing the relationship between the amount of flame retardant, which is a raw material of a neutron shielding material, and the oxygen index. [Figure 6B] FIG. 1 is a diagram showing the relationship between the amount of flame retardant, which is a raw material of a neutron shielding material, and dimensional error. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0030] Hereinafter, a neutron shielding material, a manufacturing method for the neutron shielding material, and a spent fuel assembly storage container equipped with the neutron shielding material according to an embodiment of the present invention will be described with reference to the drawings. In the following drawings, common components are denoted by the same reference numerals, and duplicated descriptions will be omitted.
[0031] Fig. 1 is a perspective view showing an example of a spent fuel assembly storage container according to an embodiment of the present invention, in which a part of the storage container for storing spent fuel assemblies is cut away to show its internal structure and cross-sectional structure. As shown in Figure 1, the storage container 1 of this embodiment includes an inner container 2, an outer container 3, a fin 4, a basket 5, a neutron shielding material 6, a primary lid 7, a secondary lid 8, and a trunnion 9.
[0032] The storage vessel 1 is a spent fuel assembly storage vessel used for storing or transporting spent fuel assemblies, and can function as a dry cask for dry storage of spent nuclear fuel. The vessel body of the storage vessel 1 is formed into a hollow cylindrical shape by an inner vessel 2 and an outer vessel 3. The inside of the storage vessel 1 stores, for example, spent fuel assemblies that have been used in a nuclear reactor and then primarily cooled in a cooling pool.
[0033] The inner vessel 2 is a vessel that houses spent fuel assemblies. The inner vessel 2 is formed, for example, of a cylindrical inner tube and a bottom plate. The inner vessel 2 is formed of carbon steel, low alloy steel, or the like. The outer vessel 3 is a vessel that houses the inner vessel 2. The outer vessel 3 is formed, for example, of a cylindrical outer tube and a bottom plate. The outer vessel 3 is formed of carbon steel, or the like.
[0034] Fins 4, which are metal plates, are provided on the side surface of the inner vessel 2. The fins 4 are provided to efficiently dissipate heat generated by the spent fuel assemblies. The fins 4 are formed, for example, from copper, aluminum, or an alloy thereof. A plurality of fins 4 are provided at intervals from each other along the circumferential direction of the inner vessel 2. The fins 4 are joined between the outer circumferential surface of the inner vessel 2 and the inner circumferential surface of the outer vessel 3.
[0035] The basket 5 is a member for storing spent fuel assemblies, and is installed inside the inner vessel 2. The basket 5 forms mutually partitioned lattice-like compartments parallel to the central axis of the storage vessel 1. The basket 5 stores, for example, about 30 to 70 spent fuel assemblies (not shown). The basket 5 supports the spent fuel assemblies in a state where they are separated from each other, and removes heat generated by the spent fuel assemblies by thermal conduction or the like.
[0036] The upper opening of the inner vessel 2 is covered by a primary lid 7. The primary lid 7 is covered by a secondary lid 8. The spent fuel assemblies are sealed inside the inner vessel 2 by a double structure consisting of the inner primary lid 7 and the outer secondary lid 8. The primary lid 7 is made of carbon steel, low alloy steel, etc. The secondary lid 8 is made of carbon steel, stainless steel, etc.
[0037] A plurality of trunnions 9 are provided on the side of the outer container 3. The trunnions 9 function as parts for supporting the storage container 1 on a storage stand or a support stand, etc., and as parts for fixing the storage container 1 to a transportation hoist, etc. When the storage container 1 is stored or transported, the trunnions 9 are fixed to the storage stand or a support stand installed in the vicinity to prevent the storage container 1 from tipping over or falling.
[0038] A space is formed between the inner container 2 and the outer container 3. Fins 4 extend between the inner container 2 and the outer container 3 along the radial direction of the inner container 2. A plurality of fins 4 are arranged at intervals between the inner container 2 and the outer container 3, thereby forming a space sandwiched between the fins 4. In addition, a closed space is formed inside the lid body formed by the primary lid 7 and the secondary lid 8, and at the bottom of the inner container 2 and the outer container 3.
[0039] The storage vessel 1 is provided with a neutron shielding material 6 so as to surround the spent fuel assemblies from the outside. The neutron shielding material 6 shields neutrons emitted from the spent fuel assemblies to the outside. The neutron shielding material 6 is made of a hardened material obtained by thermally hardening a raw material liquid in which a base agent, a hardener, a hardening accelerator, a flame retardant, and a neutron absorbing material are mixed. The neutron shielding material 6 is placed in the space between the fins 4 between the inner vessel 2 and the outer vessel 3, in the space inside the lid body formed by the primary lid 7 and the secondary lid 8, and in the space at the bottom of the inner vessel 2 and the outer vessel 3.
[0040] The neutron shielding material according to this embodiment is a neutron shielding material made of epoxy resin, the main component of which is epoxy resin. The neutron shielding material according to this embodiment is composed of a cured product of a resin composition including a base agent containing a compound containing two epoxy groups in the molecule, a curing agent which causes ring-opening polymerization of the epoxy groups, a curing accelerator which promotes the curing reaction of the base agent and the curing agent, a flame retardant which makes the resin flame retardant, and a neutron absorbing material which absorbs neutrons.
[0041] The neutron shielding material according to this embodiment is obtained as a cured resin composition by preparing a raw material liquid of a resin composition in which a base agent, a curing agent, a curing accelerator, a flame retardant, and a neutron absorbing material are mixed, and then thermally curing the raw material liquid at an atmospheric temperature of 45° C. to 55° C. By using a predetermined base agent, curing agent, curing accelerator, etc. and thermally curing at an atmospheric temperature of 45° C. to 55° C., it is possible to achieve both high heat resistance and neutron shielding and sealing performance.
[0042] In this specification, heat resistance performance means the ability to withstand high heat, and refers to performance evaluated using the glass transition temperature and thermal distortion temperature (thermal deformation temperature) as indicators. When a neutron shielding material is used in a spent fuel assembly storage container, the neutron shielding material is exposed to high temperatures for a long period of time due to the generation of decay heat from the spent fuel. When the neutron shielding material is exposed to high temperatures for a long period of time, thermal degradation and aging degradation of the resin occur. As the degradation progresses, the hydrogen density or number of hydrogen decreases, causing mass loss, and the neutron shielding performance, etc. deteriorates. Therefore, the neutron shielding material is required to have high shielding performance even after being exposed to high temperatures for a long period of time.
[0043] The heat resistance of a neutron shielding material can be evaluated by measuring the glass transition temperature and heat distortion temperature. The shielding performance of a neutron shielding material can also be indirectly evaluated using the rate of decrease in hydrogen density or number of hydrogen atoms over time and the rate of mass loss as indicators. A neutron shielding material changes over time due to thermal deterioration and aging of the resin, causing a decrease in hydrogen density or number of hydrogen atoms and mass loss, and a large decrease in molecular weight, which causes a decrease in glass transition temperature and heat distortion temperature. Therefore, the heat resistance of a neutron shielding material can be evaluated by comparing the glass transition temperature and heat distortion temperature in the initial state with the glass transition temperature and heat distortion temperature in the deteriorated state to confirm that they have not decreased significantly even after deterioration.
[0044] In this specification, neutron shielding performance means the ability to shield neutrons that pass through the neutron shielding material. When a neutron shielding material is used in a spent fuel assembly storage container, neutrons are emitted from the spent fuel, which may cause a risk of exposure to workers and radiation effects on the surrounding area. Therefore, the neutron shielding material is required to have high neutron shielding performance.
[0045] The neutron shielding performance of a neutron shielding material can be evaluated by placing the neutron shielding material against a neutron source and determining the dose rate of the neutron flux at a position 1 m away from the surface of the neutron shielding material opposite the neutron source. The dose rate can be determined by a dosimeter or neutron transport calculation. The neutron shielding performance of a neutron shielding material can also be indirectly evaluated using the decrease rate of hydrogen density or number of hydrogen atoms or the mass loss rate over time as indicators. The neutron shielding performance of a neutron shielding material changes over time due to thermal degradation and aging of the resin, resulting in a decrease in hydrogen density or number of hydrogen atoms, mass loss, and a decrease in glass transition temperature and thermal distortion temperature. Therefore, the shielding performance of a neutron shielding material can be evaluated by comparing the hydrogen density or number of hydrogen atoms or mass in the initial state with the hydrogen density or number of hydrogen atoms or mass in the deteriorated state to confirm that there is no significant decrease even after deterioration. In addition, the shielding performance of a neutron shielding material can be evaluated by comparing the glass transition temperature and thermal distortion temperature in the initial state with the glass transition temperature and thermal distortion temperature in the deteriorated state to confirm that they have not significantly decreased even after deterioration.
[0046] In this specification, sealing performance means the performance of sealing radioactive material in a predetermined space by the neutron shielding material. When the neutron shielding material is used in a spent fuel assembly storage container, if the radioactive material is not hermetically surrounded by the surrounding neutron shielding material, there is a risk that the radioactive material itself or the radiation emitted by the radioactive material will leak directly to the outside. The area not surrounded by the neutron shielding material will be an area where the neutron shielding performance of the neutron shielding material cannot be obtained. Therefore, the neutron shielding material is required to have high sealing performance.
[0047] The sealing performance of the neutron shielding material can be evaluated by determining the dimensional accuracy of the neutron shielding material with respect to the installation location and the volume occupancy rate of the neutron shielding material with respect to the target shape. The sealing performance of the neutron shielding material is affected by the shape and volume of the neutron shielding material arranged to surround the shielding target. In addition, the sealing performance of the neutron shielding material changes over time due to thermal deterioration and aging deterioration of the resin, and voids are generated when the resin components volatilize. This leads to a decrease in the dimensional accuracy with respect to the installation location and a decrease in the volume occupancy rate with respect to the target shape. Therefore, the sealing performance of the neutron shielding material can be evaluated by comparing the dimensions in the initial state with the dimensions after deterioration, and comparing the volume occupancy rate with respect to the target shape in the initial state with the volume occupancy rate with respect to the target shape in the deteriorated state, thereby confirming that the sealing performance has not decreased significantly even after deterioration.
[0048] The dimensional accuracy of the installation location and the volume occupancy rate of the target shape are affected by the fluidity and hardening speed of the raw material liquid. For example, if the viscosity of the raw material liquid is high, the resin flow to the mold will be poor, and the raw material liquid will not harden or be molded according to the target shape, resulting in low dimensional accuracy of the installation location. In addition, if there is a temperature difference between parts of the raw material liquid and the hardening speed of the raw material liquid is not uniform, the parts will harden at different hardening speeds, and sink marks will easily occur at the four corners of the hardened product, resulting in a small volume occupancy rate of the target shape. In addition, if the hardening speed of the raw material liquid is extremely fast, it becomes difficult for the air entrained from the raw material liquid during the hardening reaction to move, and bubbles and voids will easily form inside the hardened product, resulting in a small volume occupancy rate of the target shape. Bubbles and voids inside the hardened product may also be formed when thermal runaway occurs during the hardening reaction and a decomposition reaction that generates gas progresses.
[0049] The dimensional accuracy of the neutron shielding material can be confirmed by measuring the length, width, height, thickness, etc. of any part of the cured material with a gauge, a three-dimensional shape measuring device, etc. The cured material may be molded by pouring the raw material liquid into the space where the neutron shielding material is to be installed, or by pouring the raw material liquid into a mold having the same dimensions as the space where the neutron shielding material is to be installed. The change in the volume occupancy rate due to sink marks can be confirmed by measuring the depth and volume of the sink marks with respect to the outline corresponding to the design target shape of the cured material with a gauge, a three-dimensional shape measuring device, etc. The change in the volume occupancy rate due to bubbles and voids can be confirmed by cutting out any cross section of the cured material and measuring the area ratio of the bubbles and voids on the cross section by image analysis, etc.
[0050] The base agent of the neutron shielding material is a component that forms an epoxy resin by a curing reaction. An epoxy compound containing two epoxy groups in the molecule is used as the base agent. Generally, epoxy resins include bisphenol A type, bisphenol E type, bisphenol F type, etc. These epoxy resins containing two epoxy groups in the molecule have fluidity near room temperature and can be cured at low temperatures near room temperature, so they have excellent filling properties for the installation location of the neutron shielding material and the molding die. Therefore, epoxy resins containing two epoxy groups in the molecule can ensure high neutron shielding performance and sealing performance.
[0051] As the base material, hydrogenated bisphenol A diglycidyl ether (hydrogenated BADGE) is used among epoxy compounds. In this specification, hydrogenation means that the aromatic ring in the molecule is hydrogenated. As the base material, hydrogenated BADGE, which is a monomer, or a prepolymer of hydrogenated BADGE, which is a polymer, can be used. Hydrogenated bisphenol A type epoxy resin has a rigid ring structure and has a high hydrogen density compared to bisphenol A diglycidyl ether, bisphenol E diglycidyl ether, bisphenol F diglycidyl ether, hydrogenated bisphenol E type epoxy resin, hydrogenated bisphenol F type epoxy resin, etc., so that it can achieve both heat resistance and neutron shielding performance at a high level.
[0052] The curing agent is a component that crosslinks the main components by ring-opening polymerization of the epoxy groups of the main component and hardens the epoxy resin. The curing agent is a derivative of 3,6-endomethylenetetrahydrophthalic anhydride to which an alkyl group is bonded (alkylnadic anhydride), and at least two or more selected from the group consisting of 4-alkylendomethylenetetrahydrophthalic anhydride, 7-alkylendomethylenetetrahydrophthalic anhydride, and endomethylenealkyltetrahydrophthalic anhydride are used. The curing agent preferably does not contain any component other than the derivative of tetrahydrophthalic anhydride to which an alkyl group is bonded. The characteristic of these curing agent structures is that even if they are decomposed by heat, only low molecular weight components derived from the alkyl group such as methane, ethane, and propane are volatilized, and decomposition that reduces the molecular weight by half is unlikely to occur. This suppresses the decrease in hydrogen density, number of hydrogen, or mass, and allows the glass transition temperature and heat distortion temperature to be maintained at a high level.
[0053] A preferred form of 4-alkyl-end methylene tetrahydrophthalic anhydride is represented by the following structural formula (1). In the structural formula (1), R1 represents an alkyl group. Examples of the alkyl group of R1 include a methyl group, an ethyl group, an n-propyl group, and an i-propyl group. If the alkyl group is one of these, it becomes easy to synthesize the curing agent and to reduce the viscosity of the raw material liquid. Furthermore, when the thermal decomposition product is analyzed by a mass spectrometer, only low molecular weight components derived from the alkyl group are detected, and high molecular weight components such as maleic anhydride are not detected, so that the decrease in hydrogen density, number of hydrogen atoms, and mass is suppressed, and a high glass transition temperature and heat distortion temperature can be maintained. [ka]
[0054] A preferred form of 7-alkyl-end methylene tetrahydrophthalic anhydride is represented by the following structural formula (2). In the structural formula (2), R2 represents an alkyl group. Examples of the alkyl group of R2 include a methyl group, an ethyl group, an n-propyl group, and an i-propyl group. If the alkyl group is one of these, synthesis of the curing agent and reduction of the viscosity of the raw material liquid become easy. Furthermore, when the thermal decomposition product is analyzed by a mass spectrometer, only low molecular weight components derived from the alkyl group are detected, and high molecular weight components such as maleic anhydride are not detected, and the decrease in hydrogen density, number of hydrogen atoms, and mass is suppressed, and a high glass transition temperature and heat distortion temperature can be maintained. [ka]
[0055] A preferred form of endomethylene alkyl tetrahydrophthalic anhydride is represented by the following structural formula (3). In the structural formula (3), R3 represents an alkyl group. Examples of the alkyl group of R3 include a methyl group, an ethyl group, an n-propyl group, and an i-propyl group. If the alkyl group is one of these, synthesis of the curing agent and reduction of the viscosity of the raw material liquid become easy. Furthermore, when the thermal decomposition product is analyzed by a mass spectrometer, only low molecular weight components derived from the alkyl group are detected, and high molecular weight components such as maleic anhydride are not detected, so that the decrease in hydrogen density, number of hydrogen atoms, and mass is suppressed, and a high glass transition temperature and heat distortion temperature can be maintained. [ka]
[0056] As the derivatives of tetrahydrophthalic anhydride having an alkyl group bonded thereto, stereoisomers of the compounds represented by structural formulas (1), (2) and (3) may be used. The derivatives of tetrahydrophthalic anhydride and their stereoisomers can be synthesized by the Diels-Alder reaction from a cyclopentadiene derivative and maleic anhydride. As the stereoisomers, the endo-adduct is usually produced as the main component, but as the curing agent, the endo-adduct, the exo-adduct or both can be used.
[0057] Stereoisomers of 4-alkyl endo methylene tetrahydro phthalic anhydride include an endo adduct represented by the following structural formula (4) and an exo adduct represented by the following structural formula (5). As the curing agent, any of the endo adduct represented by structural formula (4), the exo adduct represented by structural formula (5), and a mixture thereof may be used. [ka] [ka]
[0058] Stereoisomers of 7-alkyl endo methylene tetrahydro phthalic anhydride include an endo adduct represented by the following structural formula (6) and an exo adduct represented by the following structural formula (7). As the curing agent, any of the endo adduct represented by structural formula (6), the exo adduct represented by structural formula (7), and a mixture thereof may be used. [ka] [ka]
[0059] Stereoisomers of endomethylenealkyltetrahydrophthalic anhydride include an endo adduct represented by the following structural formula (8) and an exo adduct represented by the following structural formula (9). As the curing agent, any of the endo adduct represented by structural formula (8), the exo adduct represented by structural formula (9), and a mixture thereof may be used. [ka] [ka]
[0060] Specific examples of 4-alkyl endomethylene tetrahydrophthalic anhydrides include endo-adducts and exo-adducts such as 4-methyl endomethylene tetrahydrophthalic anhydride (5-methyl-5-norbornene-2,3-dicarboxylic anhydride), 4-ethyl endomethylene tetrahydrophthalic anhydride (5-ethyl-5-norbornene-2,3-dicarboxylic anhydride), and 4-propyl endomethylene tetrahydrophthalic anhydride (5-propyl-5-norbornene-2,3-dicarboxylic anhydride).
[0061] Specific examples of 7-alkyl end methylene tetrahydrophthalic anhydrides include endo adducts and exo adducts such as exo 7-methyl end methylene tetrahydrophthalic anhydride (exo 7-methyl-5-norbornene-2,3-dicarboxylic anhydride), exo 7-ethyl end methylene tetrahydrophthalic anhydride (exo 7-ethyl-5-norbornene-2,3-dicarboxylic anhydride), and exo 7-propyl end methylene tetrahydrophthalic anhydride (exo 7-propyl-5-norbornene-2,3-dicarboxylic anhydride).
[0062] Specific examples of endomethylene alkyl tetrahydrophthalic anhydrides include endo-adducts and exo-adducts such as methyl endomethylene tetrahydrophthalic anhydride (methyl-5-norbornene-2,3-dicarboxylic anhydride), ethyl endomethylene tetrahydrophthalic anhydride (ethyl-5-norbornene-2,3-dicarboxylic anhydride), and propyl endomethylene tetrahydrophthalic anhydride (propyl-5-norbornene-2,3-dicarboxylic anhydride).
[0063] These derivatives of tetrahydrophthalic anhydride have a high reactivity with hydrogenated bisphenol A diglycidyl ether compared to other general curing agents. Therefore, it is possible to cure the raw material liquid in which the base agent, the curing agent, etc. are mixed at a relatively low temperature. In addition, the derivatives of tetrahydrophthalic anhydride can form a cured product with a glass transition temperature of more than about 170 to 180°C, so that high heat resistance can be obtained. In addition, compared to general curing agents such as acid anhydrides, the hydrogen density is high, so that high neutron shielding performance can be obtained.
[0064] In addition, many derivatives of tetrahydrophthalic anhydride are liquid at room temperature, and can be easily liquefied by mixing them with stereoisomers. Therefore, a curing agent that is liquid at room temperature can be easily prepared. The use of a liquid curing agent makes it possible to prepare a liquid raw material liquid with low viscosity and to mold a cured product by casting the liquid raw material liquid. This improves the flow of resin into the mold and improves the moldability of the neutron shielding material, resulting in high sealing performance.
[0065] As the curing agent, of 4-alkylendomethylenetetrahydrophthalic anhydride, 7-alkylendomethylenetetrahydrophthalic anhydride, and endomethylenealkyltetrahydrophthalic anhydride, it is preferable to use two types, 4-alkylendomethylenetetrahydrophthalic anhydride and 7-alkylendomethylenetetrahydrophthalic anhydride.
[0066] 4-alkyl end methylene tetrahydrophthalic anhydride represented by structural formula (1) and 7-alkyl end methylene tetrahydrophthalic anhydride represented by structural formula (2) have a structure that is more stable against heat than end methylene alkyl tetrahydrophthalic anhydride represented by structural formula (3). End methylene alkyl tetrahydrophthalic anhydride has a structure in which the structure that crosslinks the main components is easily broken when the alkyl group is eliminated by thermal decomposition. In contrast, in 4-alkyl end methylene tetrahydrophthalic anhydride and 7-alkyl end methylene tetrahydrophthalic anhydride, even if the alkyl group is eliminated by thermal decomposition, the bond near the alkyl group such as the α-position is easily broken. Therefore, even if decomposition due to deterioration progresses, the structure is unlikely to become low molecular weight, and the structure that crosslinks the main components is unlikely to be broken, so the degree of polymerization of the epoxy resin is likely to be maintained. Even if thermal degradation or aging deterioration progresses, a high glass transition temperature is maintained, which is advantageous for maintaining high heat resistance performance for a long period of time.
[0067] The amount of the curing agent is preferably 50 parts by mass or more and 75 parts by mass or less per 100 parts by mass of the base resin. If the amount of the curing agent is less than 50 parts by mass, the glass transition temperature of the cured product tends to be low, and there is a risk of the heat resistance being reduced. On the other hand, if the amount of the curing agent is more than 75 parts by mass, the epoxy resin is plasticized, and the glass transition temperature of the cured product is reduced. If the amount of the curing agent is 50 parts by mass or more and 75 parts by mass or less, a high glass transition temperature is obtained, and therefore high heat resistance can be ensured.
[0068] The hardening accelerator is a component that accelerates the hardening reaction between the main agent and the hardener. As the hardening accelerator, a compound that is solid or semi-solid at room temperature and has a melting point of 30°C or more and 45°C or less is used. The hardening accelerator used as a raw material for the neutron shielding material according to this embodiment has a low melting point or freezing point and an extremely slow rate of crystal nucleus (solid) generation, and therefore has the characteristic of being able to exist in a mixed state of liquid and solid.
[0069] In this specification, room temperature means a temperature of 1°C or more and less than 30°C. The temperature in a warehouse where the raw materials of the neutron shielding material are stored is usually included in room temperature. In this specification, semi-solid means a material form in which a solid and a liquid are mixed. Such a material form can occur when crystals (solids) are precipitated in a liquid. In a semi-solid, crystals are precipitated in a transparent liquid, so that the crystals can be confirmed with the naked eye. When the hardening accelerator, which is a single substance used as a raw material of the neutron shielding material according to this embodiment, is visually observed, it is a transparent color in liquid, but appears slightly cloudy when crystals (solids) are precipitated.
[0070] The hardening accelerator having a melting point of 30° C. or more and 45° C. or less, which is used as a raw material for the neutron shielding material according to this embodiment, is stored in a solid or semi-solid state, melted by heating, and then mixed with the base agent, hardener, etc. It is preferable that the raw material for the neutron shielding material according to this embodiment does not contain any components other than the compound having a melting point of 30° C. or more and 45° C. or less as the hardening accelerator.
[0071] In general, a curing accelerator that is liquid at room temperature has a drawback that the reaction activity of the curing reaction is low because the self-decomposition reaction at room temperature is suppressed. When a liquid curing accelerator is used, the degree of polymerization is difficult to increase, and the curing reaction does not proceed unless sufficient heating or the like is performed. In addition, a curing accelerator that is liquid at room temperature has a drawback that it is easily deteriorated if it is stored in an unsealed state for a long period of time in a high temperature or humid storage environment. Since oxygen, which is a deterioration factor, easily diffuses in the liquid, the curing accelerator is easily decomposed. When the curing accelerator is decomposed, the concentration in the raw material liquid decreases, making it more difficult for the curing reaction to proceed.
[0072] On the other hand, curing accelerators with a melting point of 50°C or higher must be heated to about 60°C or higher to melt them in order to mix uniformly with the base agent and curing agent. However, when heated to a high temperature, there is a risk of thermal runaway due to the synergy with the heat generated by the curing reaction. When the raw material liquid is heated to about 60°C or higher, thermal runaway occurs and the temperature easily rises to 100°C or higher, making it easy for a decomposition reaction accompanied by gas generation to occur. The generation of gas causes bubbles and voids to form inside the cured product, causing problems such as reduced neutron shielding and sealing performance.
[0073] In contrast, when a curing accelerator that is solid or semi-solid at room temperature is used, the shelf life is improved and high curing reaction activity is obtained, so that the curing reaction can proceed uniformly and easily with a sufficiently high crosslink density even at low temperatures. In addition, if the melting point is 30°C or more and 45°C or less, there is no need to heat the raw material liquid to a high temperature of about 60°C or more, so that decomposition reactions accompanied by gas generation can be suppressed. Therefore, while suppressing the formation of bubbles and voids inside the cured product, it is possible to ensure high heat resistance, neutron shielding performance, and sealing performance by curing with high reaction activity, i.e., sufficiently high crosslink density.
[0074] However, the raw materials such as the base agent and the hardener must be prepared as liquid raw material liquid in order to mold the neutron shielding material. Since a hardening accelerator that is solid or semi-solid at room temperature is difficult to disperse uniformly in the raw material liquid, adding it to the raw material liquid in a solid or semi-solid state tends to cause variation in the hardening speed between regions in the raw material liquid. If the hardening speed varies, the hardening reaction may not proceed throughout the entire area, or the hardening reaction may proceed unevenly, causing dimensional errors or sink marks.
[0075] Therefore, it is preferable that the curing accelerator, which is solid or semi-solid at room temperature, is stored in a solid or semi-solid state and then dissolved by heating during the production of the neutron shielding material. The curing accelerator is preferably heated at an atmospheric temperature of 45°C or higher and 55°C or lower. When the heating temperature is 45°C or higher, the curing accelerator, which has a melting point of 30°C or higher and 45°C or lower, can be reliably melted. Also, when the heating temperature is 55°C or lower, thermal runaway of the curing reaction can be avoided.
[0076] The curing accelerator that is solid or semi-solid at room temperature may be melted by heating before being added to the raw material liquid, or may be melted by heating after being added to the raw material liquid. The curing accelerator that is solid or semi-solid at room temperature may be melted by heating individually, or may be melted by heating while being mixed with other components. However, from the viewpoint of uniformly progressing the curing reaction, it is preferable to melt each of the curing accelerators by heating individually, and then add them to the raw material liquid in which the base agent, the curing agent, the flame retardant, and the neutron absorbing material are mixed, and then mix them with the other components.
[0077] Also, the raw material liquid in which the base agent, hardener, flame retardant, and neutron absorber are mixed may be heated at an ambient temperature of 45°C to 55°C before adding the hardening accelerator. If the raw material liquid in which the base agent and hardener are mixed is heated in advance, it is possible to prevent the hardening accelerator from precipitating in the raw material liquid when the hardening accelerator with a melting point of 30°C to 45°C is added. However, if a hardening accelerator with a melting point of more than 45°C is used, the amount of heat required for dissolution is insufficient even when the hardening accelerator is heated at an ambient temperature of 45°C to 55°C, and the hardening accelerator remains in a semi-solid state and cannot be completely dissolved into a liquid.
[0078] As the curing accelerator, it is preferable to use 2-ethyl-4-methylimidazole, 1-benzyl-2-phenylimidazole, 1,2-dimethylimidazole, or 1-cyanoethyl-2-ethyl-4-methylimidazole. As the curing accelerator, one type of compound or multiple types of compounds may be used.
[0079] These curing accelerators are compounds with a melting point of 30°C or more and 45°C or less, which are solid or semi-solid at room temperature. Therefore, the curing reaction can proceed uniformly and easily even at low temperatures while suppressing the formation of bubbles or voids inside the cured product, thereby obtaining high neutron shielding and sealing performance. In addition, these imidazole curing accelerators provide high reactivity for accelerating the curing reaction compared to other general curing accelerators. The crosslink density of the epoxy resin increases, so the glass transition temperature increases, resulting in high heat resistance.
[0080] The amount of the curing accelerator is preferably 0.1 parts by mass or more and 4 parts by mass or less, and more preferably 1 part by mass or more and 2 parts by mass or less, relative to 100 parts by mass of the base agent. If the amount of the curing accelerator is small, the curing reaction may not proceed or may take a long time. On the other hand, if the amount of the curing accelerator is large, the curing reaction is difficult to proceed uniformly. If the amount of the curing accelerator is 0.1 parts by mass or more and 4 parts by mass or less, the curing reaction can proceed uniformly within a practical time.
[0081] The flame retardant is a component that imparts flame retardancy to the epoxy resin. As the flame retardant, any suitable type can be used as long as it does not impair the mechanical properties of the epoxy resin and is chemically stable. As the flame retardant, one type may be used, or multiple types may be used in combination.
[0082] Examples of flame retardants include metal hydroxides such as magnesium hydroxide, aluminum hydroxide, and calcium hydroxide; antimony oxides such as antimony trioxide and antimony pentoxide; hydrates of metal oxides such as alumina trihydrate; inorganic phosphorus compounds such as ammonium polyphosphate; organic phosphorus compounds such as phosphate esters and aromatic condensed phosphate esters; and halogen compounds such as hexabromobenzene and tetrabromobisphenol A.
[0083] As the flame retardant, magnesium hydroxide or aluminum hydroxide is preferable, and aluminum hydroxide is particularly preferable. These flame retardants are stable up to about 200°C, and at higher temperatures, they undergo endothermic reactions. For example, magnesium hydroxide starts to absorb heat at about 290°C to 310°C. Aluminum hydroxide starts to absorb heat at about 240°C to 260°C. Therefore, when the neutron shielding material after thermal hardening is exposed to high temperatures, it can adequately exert its flame retardant effect. When used in a spent fuel assembly storage vessel, it can more reliably suppress thermal deterioration and combustion due to decay heat that is continuously generated.
[0084] The amount of the flame retardant is preferably 150 parts by mass or more and 220 parts by mass or less per 100 parts by mass of the main component. If the amount of the flame retardant is less than 150 parts by mass, the flame retardant performance of the neutron shielding material is reduced, and the oxygen index is lower than 26. On the other hand, if the amount of the flame retardant is more than 220 parts by mass, the viscosity of the raw material liquid increases, which makes it easier for dimensional errors to occur during molding, and reduces the sealing performance of the neutron shielding material. If the amount of the flame retardant is 150 parts by mass or more and 220 parts by mass or less, the oxygen index of the neutron shielding material can be improved, and high flame retardant performance and heat resistance can be ensured.
[0085] The neutron absorbing material is a component that absorbs neutrons that pass through the epoxy resin. As the neutron absorbing material, any suitable material with a large neutron absorption cross section can be used as long as it does not impair the mechanical properties of the epoxy resin and is chemically stable. As the neutron absorbing material, one type may be used, or multiple types may be used in combination.
[0086] Examples of neutron absorbing materials include boron compounds such as boron carbide, boron nitride, boric anhydride, metaboric acid, and colemanite; elemental metals such as cadmium, hafnium, gadolinium, and samarium; and compounds such as oxides containing these elements.
[0087] As the neutron absorbing material, boron carbide or boron nitride is preferable. These neutron absorbing materials are unlikely to react with the base agent, the hardener, or the flame retardant such as magnesium hydroxide during the hardening reaction. Therefore, high neutron shielding performance can be obtained without significantly impairing the mechanical properties, hydrogen density, heat resistance, etc. of the neutron shielding material.
[0088] The amount of the neutron absorbing material is preferably 1 part by mass or more and 10 parts by mass or less per 100 parts by mass of the base material. If the amount of the neutron absorbing material is less than 1 part by mass, the neutral shielding performance of the neutron shielding material will be reduced. On the other hand, if the amount of the neutron absorbing material is more than 10 parts by mass, the viscosity of the raw material liquid will be high, which will easily cause dimensional errors during molding and will reduce the sealing performance of the neutron shielding material. If the amount of the neutron absorbing material is more than 1 part by mass and 10 parts by mass or less, high neutron shielding performance and sealing performance can be ensured.
[0089] In the neutron shielding material according to this embodiment, the glass transition temperature of the epoxy resin in the initial state immediately after the completion of the curing reaction is preferably 150° C. or higher. The glass transition temperature is preferably 155° C. or higher, more preferably 160° C. or higher, even more preferably 165° C. or higher, even more preferably 170° C. or higher, and even more preferably 175° C. or higher. In addition, the glass transition temperature is preferably 180° C. or lower.
[0090] The glass transition temperature is a value that serves as an index of heat resistance temperature. If the neutron shielding material is used for a long period of time above the glass transition temperature, there is a concern that it will deteriorate due to heat. In the neutron shielding material, the hydrogen density or number of hydrogen atoms decreases due to thermal deterioration or aging deterioration of the resin, resulting in mass loss. As such deterioration progresses, the glass transition temperature and thermal distortion temperature decrease, and the neutron shielding performance, sealing performance, etc. decrease. Therefore, the glass transition temperature of the neutron shielding material is preferably 150°C or higher, which is the upper limit of the allowable temperature of a resin neutron shielding material in dry storage applications. If the glass transition temperature is 150°C or higher, excellent heat resistance that can withstand the decay heat of spent fuel can be obtained. In addition, even if the neutron shielding material is exposed to high temperatures for a long period of time, the thermal deterioration or aging deterioration of the resin is less likely to progress, so that high neutron shielding performance and sealing performance can be maintained for a long period of time. However, if the glass transition temperature exceeds 180°C, problems arise in application such as the inability to fill every nook and cranny due to high viscosity and solidification, which is not preferable.
[0091] The neutron shielding material according to the present embodiment preferably has an oxygen index of 26 or more. To improve the heat resistance of the neutron shielding material, it is essential to improve the flame retardant performance. In general, the flame retardant performance of a resin can be expressed using the oxygen index as an index. The oxygen index is defined as the minimum oxygen concentration required for a material to sustain combustion. The oxygen index can be measured by taking a test piece from the neutron shielding material and following the flammability test method specified in JIS K 7201-2. If the oxygen index is 26 or more, the material does not fall under the category of designated combustible material and has high flame retardant performance, so that fires caused by decay heat generated by spent fuel can be prevented.
[0092] According to the neutron shielding material according to the present embodiment, the main agent is hydrogenated bisphenol A diglycidyl ether, so that a higher neutron shielding performance than the conventional one can be obtained. In addition, since the curing agent is two or more selected from the group consisting of derivatives of tetrahydrophthalic anhydride, high reaction activity can be obtained and the raw material can be easily liquefied. A short time of thermal curing with high uniformity at a low temperature close to room temperature is possible, and the glass transition temperature is increased by improving the crosslink density. Therefore, a higher heat resistance performance and sealing performance than the conventional one can be obtained. In addition, since the curing accelerator is a compound that is solid or semi-solid at room temperature with a melting point of 30°C or more and 45°C or less, the storage stability of the curing accelerator is good compared to the liquid case, high reaction activity can be obtained, and thermal curing at a low temperature close to room temperature is possible. At a low temperature close to room temperature, a highly uniform curing reaction can be promoted without generating gas due to a decomposition reaction, so that the glass transition temperature is increased by improving the crosslink density, and a higher heat resistance performance and sealing performance than the conventional one can be obtained. Therefore, it is possible to provide a neutron shielding material that achieves a higher level of heat resistance, neutron shielding performance, and sealing performance than ever before, and also has excellent storage stability of the hardening accelerator.
[0093] The neutron shielding material according to the present embodiment can be used by forming it into an appropriate shape depending on the application. The neutron shielding material according to the present embodiment can be used for various applications for shielding neutrons, but is suitable for applications where high temperatures of 150°C or more and 300°C or less may continue, for example, as a neutron shielding material 6 provided in a storage container 1 as shown in FIG. 1. The neutron shielding material according to the present embodiment is difficult to break by pyrolysis of the crosslinks formed by the hardener, and can maintain high heat resistance performance for a long period of time, so that even in a high-temperature environment, a decrease in hydrogen density or number of hydrogen and a decrease in sealing performance due to deformation of the neutron shielding material are prevented. Even when the cooling period in the cooling pool in the nuclear power plant is short or when high-burnup spent nuclear fuel assemblies are stored, it is possible to increase the number of spent nuclear fuel assemblies loaded into the cask, and it is possible to reduce the weight of the cask and reduce the volume occupied by the storage.
[0094] The neutron shielding material according to this embodiment can be installed in one or more of the following locations in a storage container 1 as shown in Fig. 1: a space between the fins 4 between the inner container 2 and the outer container 3, an internal space of a lid body formed by a primary lid 7 and a secondary lid 8, and a space at the bottom of the inner container 2 or the outer container 3. The neutron shielding material according to this embodiment may be manufactured by filling a raw material liquid of a resin composition in which a base agent, a curing agent, a curing accelerator, a flame retardant, and a neutron absorbing material are mixed, into a space where the neutron shielding material is to be installed and curing the raw material liquid, or by filling a predetermined mold and curing the raw material liquid.
[0095] Furthermore, the neutron shielding material according to the present embodiment can be applied to the radiation shielding portion of a container for storing or transporting radioactive materials, such as a radioactive material transport container, a radioactive material storage container, etc., in addition to the spent fuel assembly storage container. It can also be applied to the radiation shielding portion provided in a facility that handles radioactive materials, such as an atomic fuel reprocessing facility, a spent nuclear fuel storage facility, an accelerator facility, etc.
[0096] FIG. 2 is a diagram showing a method for manufacturing a neutron shielding material according to an embodiment of the present invention. As shown in Fig. 2, the neutron shielding material according to the present embodiment can be manufactured by thermally curing a raw material liquid in which raw materials are mixed. The manufacturing method of the neutron shielding material according to the present embodiment includes a raw material heating step S1, a raw material liquid preparation step S2, a casting step S3, and a thermal curing step S4.
[0097] The raw material heating step S1 is a step for heating the raw materials of the neutron shielding material. In the raw material heating step S1, the hardening accelerator and other raw materials that are solid or semi-solid at room temperature are preheated by heating before the hardening reaction. By heating the raw materials, the solid or semi-solid components can be melted, and the raw material liquid obtained by mixing the raw materials can be made low-viscosity.
[0098] The raw materials of the neutron shielding material are preferably heated at an atmospheric temperature of 45° C. or more and 55° C. or less. In the raw material heating step S1, at least the hardening accelerator is heated and melted, but one or more of the other raw materials, the base agent, the hardening agent, the flame retardant, and the neutron absorbing material, may also be heated. The base agent, the hardening agent, and the hardening accelerator are preferably heated separately so as not to initiate a hardening reaction.
[0099] The curing accelerator may be one or more selected from the group consisting of 2-ethyl-4-methylimidazole, 1-benzyl-2-phenylimidazole, 1,2-dimethylimidazole, and 1-cyanoethyl-2-ethyl-4-methylimidazole. The amount of the curing accelerator is preferably 0.1 to 4 parts by mass, more preferably 1 to 2 parts by mass, per 100 parts by mass of the base agent.
[0100] The raw material liquid preparation step S2 is a step of mixing the raw materials of the neutron shielding material to prepare a raw material liquid. In the raw material liquid preparation step S2, the raw materials of the neutron shielding material are mixed while being heated. By mixing while being heated, it is possible to reduce the viscosity of the raw material liquid obtained by mixing the raw materials while preventing precipitation of components that are solid or semi-solid at room temperature, such as a hardening accelerator.
[0101] The raw material liquid is preferably mixed while being heated at an ambient temperature of 45°C or more and 55°C or less. In the raw material liquid preparation step S2, it is preferable to first mix the base material, the curing agent, the flame retardant, and the neutron absorbing material. It is preferable to add the hardening accelerator, which is solid or semi-solid at room temperature, to the mixed liquid in which these are mixed while heating the mixed liquid. By mixing or adding while heating, precipitation of the hardening accelerator can be prevented.
[0102] The base material may be hydrogenated BADGE, which is a monomer, or a prepolymer of hydrogenated BADGE, which is a polymer. The curing agent may be at least two selected from the group consisting of 4-alkyl endomethylene tetrahydrophthalic anhydride, 7-alkyl endomethylene tetrahydrophthalic anhydride, and endomethylene alkyl tetrahydrophthalic anhydride. The alkyl groups of the curing agent are preferably methyl, ethyl, or propyl. The blending amount of the curing agent is preferably 50 parts by mass or more and 75 parts by mass or less per 100 parts by mass of the base material. The blending amount of the flame retardant is preferably 150 parts by mass or more and 220 parts by mass or less per 100 parts by mass of the base material. The blending amount of the neutron absorbing material is preferably 1 part by mass or more and 10 parts by mass or less per 100 parts by mass of the base material.
[0103] The casting step S3 is a step of casting a raw material liquid in which the raw materials of the neutron shielding material are mixed into a mold. In the casting step S3, the raw material liquid is cast into a mold according to the target shape of the neutron shielding material. By casting into the mold and thermally curing, the neutron shielding material, which is a cured product of the epoxy resin, can be molded into the desired shape.
[0104] As the mold, depending on the application and target shape of the neutron shielding material, the space where the neutron shielding material is installed may be used, or a mold for resin molding may be used. The raw material liquid is preferably cast while being heated at an atmospheric temperature of 45° C. or more and 55° C. or less. Casting while being heated can prevent precipitation of the curing accelerator.
[0105] The thermal curing step S4 is a step of thermally curing the raw material liquid in which the raw materials of the neutron shielding material are mixed. In the thermal curing step S4, the base agent and the curing agent contained in the raw material liquid are polymerized by a curing reaction. By carrying out the curing reaction, a cured product that functions as a neutron shielding material molded into a predetermined shape can be obtained. The cured product obtained by the curing reaction does not substantially contain a solid or semi-solid curing accelerator, but contains the curing accelerator after the reaction in a molten state.
[0106] The raw material liquid can be thermally cured at an atmospheric temperature of room temperature or higher and 55° C. or lower. For example, after casting while heating at an atmospheric temperature of 45° C. or higher and 55° C. or lower, the curing reaction can be allowed to proceed by leaving it at room temperature or by heating it. From the viewpoint of shortening the curing time, the curing temperature is preferably 30° C. or higher and 55° C. or lower, and more preferably 45° C. or higher and 55° C. or lower.
[0107] According to this method for producing a neutron shielding material, the curing accelerator, which has a melting point of 30°C or more and 45°C or less and is solid or semi-solid at room temperature, is melted in advance before the start of the curing reaction, so that the curing speed is less likely to vary in the raw material liquid. The curing reaction is more likely to proceed uniformly throughout the raw material liquid, and dimensional errors and sink marks in the cured product can be reduced, resulting in high sealing performance. In addition, since the raw material liquid is cured at a low temperature near room temperature, thermal runaway of the curing reaction can be avoided and the curing can be performed uniformly. Air bubbles and voids are less likely to form inside the cured product, so that high neutron shielding performance and sealing performance can be obtained.
[0108] Although the embodiment of the present invention has been described above, the present invention is not limited to the above embodiment, and various modifications are possible within the scope of the present invention. For example, the present invention is not necessarily limited to having all the configurations of the above embodiment. It is possible to replace a part of the configuration of an embodiment with another configuration, add a part of the configuration of an embodiment to another form, or omit a part of the configuration of an embodiment. EXAMPLES
[0109] The present invention will be specifically described below with reference to examples, but the technical scope of the present invention is not limited to these examples.
[0110] As an example, a neutron shielding material made of epoxy resin was produced, and the curing conditions of the raw material liquid, and the properties of the raw material liquid and the cured product were evaluated.
[0111] Fig. 3 is a diagram showing the relationship between the set temperature and the maximum temperature when the raw material liquid containing the raw materials of the neutron shielding material is heated and mixed. Fig. 3 shows the result of heating and mixing the raw material liquid prepared by mixing the base agent, hardener, flame retardant, and neutron absorbing material and adding a hardening accelerator to proceed with the hardening reaction. In Fig. 3, the horizontal axis shows the set temperature [°C] during heating and mixing, and the vertical axis shows the maximum temperature [°C] of the raw material liquid during heating and mixing. The straight line in the diagram shows the ambient temperature of the raw material liquid during heating and mixing.
[0112] The base resin used was hydrogenated bisphenol A type epoxy resin EP-4080E (manufactured by ADEKA Corporation).The hardener used was a mixture of 4-methylendomethylenetetrahydrophthalic anhydride (5-methyl-5-norbornene-2,3-dicarboxylic anhydride), 7-methylendomethylenetetrahydrophthalic anhydride (exo-7-methyl-5-norbornene-2,3-dicarboxylic anhydride), and methylendomethylenetetrahydrophthalic anhydride (methyl-5-norbornene-2,3-dicarboxylic anhydride).
[0113] The curing accelerator used was 2-ethyl-4-methylimidazole (2E4MZ) (manufactured by Shikoku Kasei Co., Ltd.), the flame retardant used was aluminum hydroxide CL-310 (manufactured by Sumitomo Chemical Co., Ltd.), and the neutron absorbing material used was boron carbide powder F-400 (manufactured by Denka Co., Ltd.).
[0114] The amount of the hardener was 60 parts by mass per 100 parts by mass of the base material. The amount of the hardening accelerator was 3 parts by mass per 100 parts by mass of the base material. The amount of the flame retardant was 200 parts by mass per 100 parts by mass of the base material. The amount of the neutron absorbing material was 8 parts by mass per 100 parts by mass of the base material.
[0115] As shown in Fig. 3, when the set temperature is in the range of 40°C or less, the maximum temperature of the raw material liquid is lower than the ambient temperature, and is 40°C or less. In such a range, the heating is insufficient, so it is difficult to completely melt the curing accelerator, which has a melting point of 30°C to 45°C. In such a range, heat generation due to the curing reaction is difficult to occur, so the maximum temperature of the raw material liquid becomes lower than the ambient temperature, and the curing reaction does not proceed easily.
[0116] On the other hand, when the set temperature was in the range of 60°C or higher, the combination of the heating of the raw material liquid and the heat generated by the curing reaction caused a rapid increase in the maximum temperature of the raw material liquid. The maximum temperature of the raw material liquid exceeded 70°C, the temperature at which thermal runaway occurs, and rose to over 100°C. In this range, a decomposition reaction accompanied by the generation of gas occurs, making it easy for air bubbles and voids to remain inside the cured product.
[0117] Therefore, it is preferable to thermally cure the raw material liquid obtained by mixing the raw materials of the neutron shielding material at an ambient temperature of 55° C. or less. It is also preferable to melt the curing accelerator in advance, and it is preferable to thermally cure the raw material liquid at a temperature of 55° C. or less and higher than about room temperature. When filling the raw material liquid into a space where the neutron shielding material is to be installed and curing the raw material liquid, or filling the raw material liquid into a predetermined mold and curing the raw material liquid, it is preferable to adjust the ambient temperature of the space to a temperature between room temperature and 55° C.
[0118] Figure 4 shows the relationship between the set temperature and the hardening time when the raw material liquid of the neutron shielding material is heated and mixed. Figure 4 shows the result of the raw material liquid prepared by mixing the base agent, hardener, flame retardant, and neutron absorbing material and adding a hardening accelerator, being heated and mixed to promote the hardening reaction. In Figure 4, the horizontal axis shows the set temperature [°C] during the heating and mixing, and the vertical axis shows the hardening time [h] from the start of heating and mixing the raw material liquid to the complete hardening of the raw material liquid.
[0119] The raw materials for the neutron shielding material were of the same type and in the same amounts as in Figure 3. In Figure 4, the atmospheric temperature during heating and mixing was the same as the set temperature.
[0120] As shown in FIG. 4, the higher the set temperature during heating and mixing, the shorter the curing time of the raw material liquid. It can be said that if the raw material liquid is thermally cured at an ambient temperature between room temperature and 55°C, a cured product can be obtained without thermal runaway. It can also be said that the higher the ambient temperature is below 55°C, the more likely it is that a cured product can be obtained in an ideal curing time shorter than room temperature. The ideal curing time means a time during which the curing reaction is likely to proceed uniformly, and does not cause sink marks on the surface of the cured product or bubbles or voids inside the cured product, and is a practical length of time for manufacturing. In fact, it was confirmed by visual observation of the cross section that no bubbles were generated inside the neutron absorber after curing at a set temperature of 55°C or less.
[0121] It was estimated that the ideal curing time for the raw material liquid containing the raw materials for the neutron shielding material is between 10 and 40 hours. In FIG. 4, the ambient temperature for the curing time of 40 hours is 45°C or higher. Also, the ambient temperature for the curing time of 10 hours is 55°C or higher. Therefore, it can be said that it is particularly preferable to thermally cure the raw material liquid containing the raw materials for the neutron shielding material at an ambient temperature of between 45°C and 55°C.
[0122] [Table 1]
[0123] Table 1 shows typical curing accelerators and the physical properties of epoxy resins to which they are added. In Table 1, the melting point indicates the melting point (°C) of the curing accelerator. The glass transition temperature indicates the glass transition temperature (°C) of the epoxy resin produced by adding the curing accelerator.
[0124] The base resin used was hydrogenated bisphenol A type epoxy resin EP-4080E (ADEKA). The hardener used was a mixture of 4-methyl-end-methylene tetrahydrophthalic anhydride, exo-7-methyl-end-methylene tetrahydrophthalic anhydride, and methyl-end-methylene tetrahydrophthalic anhydride (methylhimic anhydride). The flame retardant used was aluminum hydroxide CL-310 (Sumitomo Chemical). The neutron absorbing material used was boron carbide powder F-400 (Denka).
[0125] The amount of the hardener was 60 parts by mass per 100 parts by mass of the base material. The amount of the hardening accelerator was 3 parts by mass per 100 parts by mass of the base material. The amount of the flame retardant was 200 parts by mass per 100 parts by mass of the base material. The amount of the neutron absorbing material was 8 parts by mass per 100 parts by mass of the base material.
[0126] First, the curing accelerator, which is solid or semi-solid at room temperature, was placed in a thermostatic chamber at 50°C for 12 hours or more to dissolve it in advance. The base resin, curing agent, and curing accelerator were mixed while being heated at an ambient temperature of 50°C to prepare a raw material liquid. The raw material liquid was then thermally cured at an ambient temperature of 55°C or less. The glass transition temperature of the epoxy resin was then measured. The glass transition temperature was determined as the temperature at which an inflection point occurred in the increase in thermal strain (thermal deformation) with increasing temperature.
[0127] The method for setting the ambient temperature during heating and mixing is as follows. First, when mixing the base material, hardener, and hardening accelerator while heating them at an ambient temperature of 50°C, a mixing tank with a heater with a temperature controller installed on the periphery is used. The temperature controller of the peripheral heater of the mixing tank is set to a temperature of about 50°C. The temperature of the outer surface of the mixing tank is measured as the ambient temperature, and the set temperature is finely adjusted so that it is 50°C. Generally, the set temperature of the temperature controller and the temperature of the outer surface of the mixing tank are equivalent. The base material, hardener, and hardening accelerator are added here and heated and mixed. Instead of the peripheral heater, hot water heated to 50°C may be circulated in the space installed on the outer layer of the mixing tank. In this case, the set temperature of the temperature controller that heats the hot water and the temperature of the outer surface of the mixing tank are also generally equivalent.
[0128] The method for setting the ambient temperature during thermal curing is as follows. First, the mold into which the raw material liquid is poured is surrounded by a non-flammable curtain. The outlet hose of the hot air heater is inserted into the space between the mold and the curtain, and hot air is blown in while measuring the ambient temperature in the space between the mold and the curtain with a thermometer. In this case, the ambient temperature is the temperature of the air in the space between the mold and the curtain. In general, the ambient temperature in the space between the mold and the curtain and the temperature of the outer surface of the mold are equivalent. Alternatively, a heater may be attached to the outer surface of the mold, and the temperature may be controlled using the heater's temperature regulator. The set temperature of the heater's temperature regulator is set to a temperature around 55°C, the temperature of the outer surface of the mold is measured as the ambient temperature, and the set temperature is fine-tuned to 55°C. In general, the set temperature of the temperature regulator and the temperature of the outer surface of the mold in the mixing tank are equivalent.
[0129] As shown in Table 1, 2-ethyl-4-methylimidazole, 1-benzyl-2-phenylimidazole, 1,2-dimethylimidazole, and 1-cyanoethyl-2-ethyl-4-methylimidazole have melting points of 30°C or higher and 45°C or lower, and are solid or semi-solid compounds at room temperature. It is clear that epoxy resins to which these curing accelerators have been added have glass transition temperatures of 150°C or higher, and exhibit high heat resistance.
[0130] [Table 2]
[0131] Table 2 shows the physical properties of the epoxy resin when a specific curing agent is added. In Table 2, the glass transition temperature shows the glass transition temperature (°C) immediately after the completion of the curing reaction of the epoxy resin prepared by adding the curing agent in a specific combination.
[0132] The base resin used was hydrogenated bisphenol A type epoxy resin EP-4080E (manufactured by ADEKA Corporation). The hardening accelerator used was 1-cyanoethyl-2-ethyl-4-methylimidazole (2E4MZ-CN). The flame retardant used was aluminum hydroxide CL-310 (manufactured by Sumitomo Chemical Co., Ltd.). The neutron absorbing material used was boron carbide powder F-400 (manufactured by Denka Co., Ltd.).
[0133] The amount of the hardener was 60 parts by mass per 100 parts by mass of the base material. The amount of the hardening accelerator was 3 parts by mass per 100 parts by mass of the base material. The amount of the flame retardant was 200 parts by mass per 100 parts by mass of the base material. The amount of the neutron absorbing material was 8 parts by mass per 100 parts by mass of the base material.
[0134] First, the curing accelerator, which is solid or semi-solid at room temperature, was placed in a thermostatic chamber at 50°C for 12 hours or more to dissolve it in advance. The base resin, curing agent, and curing accelerator were mixed while being heated at an ambient temperature of 45°C to prepare a raw material liquid. The raw material liquid was then thermally cured at an ambient temperature of 55°C or less. The glass transition temperature of the epoxy resin was then measured. The glass transition temperature was determined as the temperature at which an inflection point occurred in the increase in thermal strain (thermal deformation) with increasing temperature.
[0135] The method of setting the atmospheric temperature during heating and mixing and the method of setting the atmospheric temperature during thermal curing are the same as the conditions in Table 1, except that the temperature setting during heating and mixing is changed to 45°C. When using such a setting method, instead of using a peripheral heater, hot water heated to 45°C may be circulated in a space installed on the outer layer of the mixing tank during heating and mixing. Also, during thermal curing, a heater may be attached to the outer surface of the mold and the temperature may be controlled using the heater's temperature regulator.
[0136] As shown in Table 2, when at least two or more types selected from the group consisting of 4-alkylendomethylenetetrahydrophthalic anhydride, exo-7-alkylendomethylenetetrahydrophthalic anhydride, and alkylendomethylenetetrahydrophthalic anhydride are used as curing agents, the epoxy resin to which these curing agents are added has a glass transition temperature of 150°C or higher, and high heat resistance is obtained.
[0137] [Table 3]
[0138] Table 3 shows the physical properties of epoxy resins with a specified hardener added after thermal degradation. In Table 3, the glass transition temperature shows the glass transition temperature (°C) after thermal degradation of epoxy resins prepared by adding hardeners in a specified combination. The conditions for thermal degradation were a heating temperature of 150°C and a heating time of 15,000 hours.
[0139] The base resin used was hydrogenated bisphenol A type epoxy resin EP-4080E (manufactured by ADEKA Corporation). The hardening accelerator used was 1-cyanoethyl-2-ethyl-4-methylimidazole (2E4MZ-CN). The flame retardant used was aluminum hydroxide CL-310 (manufactured by Sumitomo Chemical Co., Ltd.). The neutron absorbing material used was boron carbide powder F-400 (manufactured by Denka Co., Ltd.).
[0140] The amount of the hardener was 60 parts by mass per 100 parts by mass of the base material. The amount of the hardening accelerator was 3 parts by mass per 100 parts by mass of the base material. The amount of the flame retardant was 200 parts by mass per 100 parts by mass of the base material. The amount of the neutron absorbing material was 8 parts by mass per 100 parts by mass of the base material.
[0141] First, the curing accelerator is solid or semi-solid at room temperature, so it was placed in a thermostatic chamber at 50°C for 12 hours or more to dissolve it in advance. The base resin, curing agent, and curing accelerator were mixed while heating at an ambient temperature of 50°C to prepare a raw material liquid. The raw material liquid was then thermally cured at an ambient temperature of 55°C or less, and the resulting cured product was subjected to a heat deterioration test. The glass transition temperature of the epoxy resin after heat deterioration was then measured. The glass transition temperature was determined as the temperature at which an inflection point occurred in the increase in thermal strain (thermal deformation) with increasing temperature.
[0142] The method of setting the ambient temperature during heating and mixing and the method of setting the ambient temperature during thermal curing are the same as the conditions in Table 1. When using such a setting method, instead of using a peripheral heater, hot water heated to 50°C may be circulated in a space installed on the outer layer of the mixing tank during heating and mixing. Also, during thermal curing, a heater may be attached to the outer surface of the mold and the temperature may be controlled using the heater's temperature regulator.
[0143] As shown in Table 3, when at least two or more types selected from the group consisting of 4-alkylendomethylenetetrahydrophthalic anhydride, exo-7-alkylendomethylenetetrahydrophthalic anhydride, and alkylendomethylenetetrahydrophthalic anhydride are used as curing agents, the epoxy resins to which these curing agents have been added have glass transition temperatures of 150°C or higher even after thermal degradation, and maintain high heat resistance.
[0144] Analysis of 4-alkyl-end-methylenetetrahydrophthalic anhydride and exo-7-alkyl-end-methylenetetrahydrophthalic anhydride by pyrolysis mass spectrometry confirmed that only the alkyl group is likely to be eliminated during thermal degradation. Even if decomposition due to degradation progresses, the bonds near the alkyl group are broken, so that the cross-linked sites are unlikely to become low molecular weight and the structure that bridges the main components is unlikely to be broken, so that a high glass transition temperature can be maintained. Even when the neutron shielding material is exposed to high temperatures for a long period of time, such as in a spent fuel assembly storage vessel, it can be said that the neutron shielding performance, heat resistance performance, and sealing performance are maintained at a high level.
[0145] Fig. 5A is a diagram showing the relationship between the amount of hardener, which is a raw material of the neutron shielding material, and the glass transition temperature. Fig. 5A shows the results of mixing the base material, hardener, flame retardant, and neutron absorbing material, adding a hardening accelerator, and mixing the raw material liquid while heating it to promote the hardening reaction. In Fig. 5A, the horizontal axis shows the amount of hardener [parts by mass] relative to 100 parts by mass of the base material, and the vertical axis shows the glass transition temperature [°C] of the epoxy resin.
[0146] The base resin used was hydrogenated bisphenol A type epoxy resin EP-4080E (manufactured by ADEKA Corporation).The hardener used was a mixture of 4-methylendomethylenetetrahydrophthalic anhydride (5-methyl-5-norbornene-2,3-dicarboxylic anhydride), 7-methylendomethylenetetrahydrophthalic anhydride (exo-7-methyl-5-norbornene-2,3-dicarboxylic anhydride), and methylendomethylenetetrahydrophthalic anhydride (methyl-5-norbornene-2,3-dicarboxylic anhydride).
[0147] The curing accelerator used was 1-benzyl-2-phenylimidazole. The flame retardant used was aluminum hydroxide CL-310 (manufactured by Sumitomo Chemical Co., Ltd.). The neutron absorbing material used was boron carbide powder F-400 (manufactured by Denka Co., Ltd.).
[0148] The amount of the curing accelerator was 3 parts by mass per 100 parts by mass of the base material. The amount of the flame retardant was 200 parts by mass per 100 parts by mass of the base material. The amount of the neutron absorbing material was 8 parts by mass per 100 parts by mass of the base material.
[0149] First, since the curing accelerator is solid or semi-solid at room temperature, it was placed in a thermostatic chamber at 50°C for 12 hours or more to dissolve it in advance. The base resin, curing agent, and curing accelerator were mixed while being heated at an ambient temperature of 50°C to prepare a raw material liquid. The raw material liquid was then thermally cured at an ambient temperature of 50°C. The glass transition temperature of the epoxy resin was then measured. The glass transition temperature was determined as the temperature at which an inflection point occurred in the increase in thermal strain (thermal deformation) with increasing temperature.
[0150] The method for setting the ambient temperature during heating and mixing is as follows. First, when mixing the base material, hardener, and hardening accelerator while heating them at an ambient temperature of 50°C, a mixing tank with a heater with a temperature controller installed on the periphery is used. The temperature controller of the peripheral heater of the mixing tank is set to a temperature of about 50°C. The temperature of the outer surface of the mixing tank is measured as the ambient temperature, and the set temperature is finely adjusted so that it is 50°C. Generally, the set temperature of the temperature controller and the temperature of the outer surface of the mixing tank are equivalent. The base material, hardener, and hardening accelerator are added here and heated and mixed. Instead of the peripheral heater, hot water heated to 50°C may be circulated in the space installed on the outer layer of the mixing tank. In this case, the set temperature of the temperature controller that heats the hot water and the temperature of the outer surface of the mixing tank are also generally equivalent.
[0151] The method for setting the ambient temperature during thermal curing is as follows. First, the mold into which the raw material liquid is poured is surrounded by a non-flammable curtain. The outlet hose of the hot air heater is inserted into the space between the mold and the curtain, and hot air is blown in while measuring the ambient temperature in the space between the mold and the curtain with a thermometer. In this case, the ambient temperature is the temperature of the air in the space between the mold and the curtain. In general, the ambient temperature in the space between the mold and the curtain and the temperature of the outer surface of the mold are equivalent. Alternatively, a heater may be attached to the outer surface of the mold, and the temperature may be controlled using the heater's temperature regulator. The set temperature of the heater's temperature regulator is set to a temperature around 55°C, the temperature of the outer surface of the mold is measured as the ambient temperature, and the set temperature is fine-tuned to 55°C. In general, the set temperature of the temperature regulator and the temperature of the outer surface of the mold in the mixing tank are equivalent.
[0152] As shown in Fig. 5A, the glass transition temperature of the epoxy resin was maximized when the amount of the curing agent was about 65 parts by mass. When the amount of the curing agent was less than 65 parts by mass, the glass transition temperature increased as the amount of the curing agent increased. On the other hand, when the amount of the curing agent was more than 65 parts by mass, the glass transition temperature decreased as the amount of the curing agent increased.
[0153] It is preferable that the glass transition temperature of the epoxy resin is 150° C. or higher. In FIG. 5A, the blending amount of the curing agent that results in a glass transition temperature of 150° C. or higher is in the range of 50 parts by mass to 75 parts by mass. Therefore, it is preferable that the blending amount of the curing agent for 100 parts by mass of the base resin is 50 parts by mass to 75 parts by mass.
[0154] Fig. 5B is a diagram showing the relationship between the amount of hardening accelerator, which is a raw material of the neutron shielding material, and the glass transition temperature. Fig. 5B shows the results of mixing the base material, hardener, flame retardant, and neutron absorbing material, adding the hardening accelerator, and mixing the raw material liquid while heating to promote the hardening reaction. In Fig. 5B, the horizontal axis shows the amount of hardening accelerator [parts by mass] relative to 100 parts by mass of the base material, and the vertical axis shows the glass transition temperature [°C] of the epoxy resin.
[0155] The base resin used was hydrogenated bisphenol A type epoxy resin EP-4080E (manufactured by ADEKA Corporation).The hardener used was a mixture of 4-methylendomethylenetetrahydrophthalic anhydride (5-methyl-5-norbornene-2,3-dicarboxylic anhydride), 7-methylendomethylenetetrahydrophthalic anhydride (exo-7-methyl-5-norbornene-2,3-dicarboxylic anhydride), and methylendomethylenetetrahydrophthalic anhydride (methyl-5-norbornene-2,3-dicarboxylic anhydride).
[0156] The curing accelerator used was 1-benzyl-2-phenylimidazole. The flame retardant used was aluminum hydroxide CL-310 (manufactured by Sumitomo Chemical Co., Ltd.). The neutron absorbing material used was boron carbide powder F-400 (manufactured by Denka Co., Ltd.).
[0157] The amount of the hardener was 60 parts by mass per 100 parts by mass of the base material. The amount of the flame retardant was 200 parts by mass per 100 parts by mass of the base material. The amount of the neutron absorbing material was 8 parts by mass per 100 parts by mass of the base material.
[0158] First, since the curing accelerator is solid or semi-solid at room temperature, it was placed in a thermostatic chamber at 50°C for 12 hours or more to dissolve it in advance. The base resin, curing agent, and curing accelerator were mixed while being heated at an ambient temperature of 50°C to prepare a raw material liquid. The raw material liquid was then thermally cured at an ambient temperature of 50°C. The glass transition temperature of the epoxy resin was then measured. The glass transition temperature was determined as the temperature at which an inflection point occurred in the increase in thermal strain (thermal deformation) with increasing temperature.
[0159] The method of setting the ambient temperature during heating and mixing and the method of setting the ambient temperature during thermal curing are the same as the conditions in Fig. 5A. When using such a setting method, instead of using a peripheral heater, hot water heated to 50°C may be circulated in a space installed on the outer layer of the mixing tank during heating and mixing. Also, during thermal curing, a heater may be attached to the outer surface of the mold and the temperature may be controlled using the heater's temperature regulator.
[0160] As shown in Fig. 5B, the glass transition temperature of the epoxy resin was maximized when the amount of the curing accelerator was about 1 to 2 parts by mass. When the amount of the curing accelerator was in the range of 1 part by mass or less, the glass transition temperature increased as the amount of the curing accelerator increased. On the other hand, when the amount of the curing accelerator was in the range of 2 parts by mass or more, the glass transition temperature decreased as the amount of the curing accelerator increased.
[0161] It is preferable that the glass transition temperature of the epoxy resin is 150° C. or higher. In FIG. 5B, the blending amount of the curing accelerator that results in a glass transition temperature of 150° C. or higher is in the range of 0.1 parts by mass to 4 parts by mass, preferably 1 part by mass to 2 parts by mass. Therefore, it is preferable that the blending amount of the curing accelerator for 100 parts by mass of the base resin is 0.1 parts by mass to 4 parts by mass, preferably 1 part by mass to 2 parts by mass.
[0162] Fig. 5C is a diagram showing the relationship between the amount of neutron absorbing material, which is a raw material of neutron shielding material, and the glass transition temperature. Fig. 5C shows the result of mixing the base material, hardener, flame retardant, and neutron absorbing material, adding a hardening accelerator, and mixing the raw material liquid while heating to promote the hardening reaction. In Fig. 5C, the horizontal axis shows the amount of neutron absorbing material [parts by mass] relative to 100 parts by mass of the base material, and the vertical axis shows the glass transition temperature [°C] of the epoxy resin.
[0163] The base resin used was hydrogenated bisphenol A type epoxy resin EP-4080E (manufactured by ADEKA Corporation).The hardener used was a mixture of 4-methylendomethylenetetrahydrophthalic anhydride (5-methyl-5-norbornene-2,3-dicarboxylic anhydride), 7-methylendomethylenetetrahydrophthalic anhydride (exo-7-methyl-5-norbornene-2,3-dicarboxylic anhydride), and methylendomethylenetetrahydrophthalic anhydride (methyl-5-norbornene-2,3-dicarboxylic anhydride).
[0164] The curing accelerator used was 1-benzyl-2-phenylimidazole. The flame retardant used was aluminum hydroxide CL-310 (manufactured by Sumitomo Chemical Co., Ltd.). The neutron absorbing material used was boron carbide powder F-400 (manufactured by Denka Co., Ltd.).
[0165] The amount of the curing accelerator was 1 part by mass per 100 parts by mass of the base material. The amount of the flame retardant was 180 parts by mass per 100 parts by mass of the base material. The amount of the curing agent was 65 parts by mass per 100 parts by mass of the base material.
[0166] First, since the curing accelerator is solid or semi-solid at room temperature, it was placed in a thermostatic chamber at 50°C for 12 hours or more to dissolve it in advance. The base resin, curing agent, and curing accelerator were mixed while being heated at an ambient temperature of 50°C to prepare a raw material liquid. The raw material liquid was then thermally cured at an ambient temperature of 50°C. The glass transition temperature of the epoxy resin was then measured. The glass transition temperature was determined as the temperature at which an inflection point occurred in the increase in thermal strain (thermal deformation) with increasing temperature.
[0167] The method of setting the ambient temperature during heating and mixing and the method of setting the ambient temperature during thermal curing are the same as the conditions in Fig. 5A. When performing such settings, instead of using a peripheral heater, hot water heated to 50°C may be circulated in a space installed on the outer layer of the mixing tank during heating and mixing. Also, during thermal curing, a heater may be attached to the outer surface of the mold and the temperature may be controlled using the heater's temperature regulator.
[0168] As shown in Figure 5C, the glass transition temperature of the epoxy resin was maximized when the amount of neutron absorbing material was about 5 parts by mass. When the amount of neutron absorbing material was 1 part by mass or less, the glass transition temperature increased as the amount of neutron absorbing material increased. On the other hand, when the amount of neutron absorbing material was 5 parts by mass or more, the glass transition temperature decreased as the amount of neutron absorbing material increased.
[0169] It is preferable that the glass transition temperature of the epoxy resin is 150° C. or higher. In FIG. 5C, the amount of the neutron absorbing material that provides a glass transition temperature of 150° C. or higher is in the range of 1 part by mass to 10 parts by mass. Therefore, it is preferable that the amount of the neutron absorbing material to be blended relative to 100 parts by mass of the base material is 1 part by mass to 10 parts by mass.
[0170] Fig. 6A is a diagram showing the relationship between the amount of flame retardant, which is a raw material for neutron shielding material, and the oxygen index. Fig. 6A shows the results of obtaining a hardened material by mixing a base material, a hardener, a flame retardant, and a neutron absorbing material, adding a hardening accelerator, and mixing the raw material liquid while heating. In Fig. 6A, the horizontal axis shows the amount of aluminum hydroxide [parts by mass] per 100 parts by mass of the base material, and the vertical axis shows the oxygen index of the hardened material.
[0171] Fig. 6B is a diagram showing the relationship between the amount of flame retardant, which is a raw material for neutron shielding material, and the dimensional error. Fig. 6B shows the results of obtaining a hardened material by mixing a base material, a hardener, a flame retardant, and a neutron absorbing material, adding a hardening accelerator, and mixing the raw material liquid while heating. In Fig. 6B, the horizontal axis shows the amount of aluminum hydroxide [parts by mass] per 100 parts by mass of the base material, and the vertical axis shows the average dimensional error [±%] of the hardened material relative to the target shape immediately after the hardening reaction is completed.
[0172] The base resin used was hydrogenated bisphenol A type epoxy resin EP-4080E (manufactured by ADEKA Corporation).The hardener used was a mixture of 4-methylendomethylenetetrahydrophthalic anhydride (5-methyl-5-norbornene-2,3-dicarboxylic anhydride), 7-methylendomethylenetetrahydrophthalic anhydride (exo-7-methyl-5-norbornene-2,3-dicarboxylic anhydride), and methylendomethylenetetrahydrophthalic anhydride (methyl-5-norbornene-2,3-dicarboxylic anhydride).
[0173] The curing accelerator used was 1-benzyl-2-phenylimidazole. The flame retardant used was aluminum hydroxide CL-310 (manufactured by Sumitomo Chemical Co., Ltd.). The neutron absorbing material used was boron carbide powder F-400 (manufactured by Denka Co., Ltd.).
[0174] The amount of the hardener was 60 parts by mass per 100 parts by mass of the base material. The amount of the hardening accelerator was 3 parts by mass per 100 parts by mass of the base material. The amount of the neutron absorbing material was 8 parts by mass per 100 parts by mass of the base material.
[0175] First, the curing accelerator, which is solid or semi-solid at room temperature, was placed in a 50°C thermostatic chamber for 12 hours or more to dissolve it in advance. The base resin, curing agent, and curing accelerator were mixed while heating at an ambient temperature of 50°C to prepare a raw material liquid. The raw material liquid was then thermally cured at an ambient temperature of 50°C. The oxygen index of the cured product and the dimensional error relative to the target shape were then measured. The oxygen index was measured by taking a test piece from the cured product and following the flammability test method specified in JIS K 7201-2.
[0176] The method of setting the ambient temperature during heating and mixing and the method of setting the ambient temperature during thermal curing are the same as the conditions in Fig. 5A. When performing such settings, instead of using a peripheral heater, hot water heated to 50°C may be circulated in a space installed on the outer layer of the mixing tank during heating and mixing. Also, during thermal curing, a heater may be attached to the outer surface of the mold and the temperature may be controlled using the heater's temperature regulator.
[0177] As shown in Fig. 6A, the oxygen index of the neutron shielding material increased as the amount of flame retardant added increased. In Fig. 6A, the amount of flame retardant added that results in an oxygen index of 26 or more is in the range of 150 parts by mass or more. Therefore, it can be said that the amount of flame retardant added to 100 parts by mass of the base material is preferably 150 parts by mass or more.
[0178] As shown in Fig. 6B, the dimensional error of the neutron shielding material with respect to the target shape increased when the amount of flame retardant exceeded a predetermined threshold. When the amount of flame retardant was 220 parts by mass or less, the dimensional error was approximately 0%. On the other hand, when the amount of flame retardant exceeded 220 parts by mass, the dimensional error increased as the amount of flame retardant increased. Therefore, it can be said that the amount of flame retardant to be mixed with 100 parts by mass of the main agent is preferably 220 parts by mass or less.
[0179] Next, as an example, a metal cask equipped with a neutron shielding material made of epoxy resin was fabricated, and the dimensional accuracy of the neutron shielding material and the performance of the neutron shielding material were evaluated. As the metal cask, a storage container as shown in FIG. 1 was fabricated.
[0180] The metal cask was a container made of a cylindrical inner and outer cylinders and a bottom plate. The inner cylinder was a steel metal cylinder that functioned as a gamma ray shield. A number of aluminum fins were attached to the side of the inner cylinder at intervals along the circumferential direction of the inner cylinder. A metal basket with cells divided into a lattice pattern to store spent fuel assemblies was attached to the inside of the inner cylinder. The opening at the top of the inner cylinder was covered with a primary lid 7 to prevent leakage of radioactive materials, and the primary lid 7 was covered with a secondary lid 8.
[0181] The base resin used was hydrogenated bisphenol A type epoxy resin EP-4080E (manufactured by ADEKA Corporation).The hardener used was a mixture of 4-methylendomethylenetetrahydrophthalic anhydride (5-methyl-5-norbornene-2,3-dicarboxylic anhydride), 7-methylendomethylenetetrahydrophthalic anhydride (exo-7-methyl-5-norbornene-2,3-dicarboxylic anhydride), and methylendomethylenetetrahydrophthalic anhydride (methyl-5-norbornene-2,3-dicarboxylic anhydride).
[0182] The curing accelerator used was 2-ethyl-4-methylimidazole (2E4MZ) (manufactured by Shikoku Kasei Co., Ltd.), the flame retardant used was aluminum hydroxide CL-310 (manufactured by Sumitomo Chemical Co., Ltd.), and the neutron absorbing material used was boron carbide powder F-400 (manufactured by Denka Co., Ltd.).
[0183] The amount of the hardener was 60 parts by mass per 100 parts by mass of the base material. The amount of the hardening accelerator was 3 parts by mass per 100 parts by mass of the base material. The amount of the flame retardant was 200 parts by mass per 100 parts by mass of the base material. The amount of the neutron absorbing material was 8 parts by mass per 100 parts by mass of the base material.
[0184] First, the hardening accelerator was heated and melted. The melted hardening accelerator was then added to the mixture of the base resin, hardener, flame retardant, and neutron absorber, and mixed to prepare the raw material liquid. For mixing, a device capable of circulating and circulating hot water heated to 45°C in the space installed on the outer layer of a large mixing tank was used. At this time, the set temperature of the temperature regulator that warms the hot water and the temperature of the outer surface of the mixing tank were roughly the same.
[0185] Next, the raw material liquid of the neutron shielding material was filled into the space between the fins of the inner and outer cylinders and into the space inside the primary lid. The filled mold was surrounded by a non-flammable curtain, and the outlet hose of a hot air heater was inserted into the space between the mold and the curtain. While measuring the atmospheric temperature in the space between the mold and the curtain with a thermometer, hot air was blown so that the atmospheric temperature reached 45°C. The raw material liquid was heated to an atmospheric temperature of 45°C and thermally cured. The curing time was about 30 hours.
[0186] Next, immediately after the completion of the hardening reaction, the dimensions of a predetermined portion of the neutron shielding material obtained by the hardening reaction were measured. As a result, it was confirmed that the dimensional error of the neutron shielding material with respect to the installation location was ±0.001% or less. Next, 70 spent fuel assemblies that had been cooled in the cooling pool for a short period were accommodated in the fabricated metal cask. As a result, the temperature of the neutron shielding material rose to about 150°C due to the decay heat of the spent nuclear fuel. However, it was confirmed by a dosimeter that the neutron shielding performance did not substantially decrease. It can be said that the neutron shielding material according to this embodiment is effective in applications where high temperatures of 150°C or more may continue. [Explanation of symbols]
[0187] 1. Storage container 2 Inner container 3 Outer container 4 Fins 5. Basket 6. Neutron Shielding Materials 7 Primary lid 8 Secondary lid 9 Trunnion
Claims
1. A neutron shielding material mainly composed of epoxy resin, The cured product is made of a resin composition including a base agent including a compound having two epoxy groups in the molecule, a curing agent that causes ring-opening polymerization of the epoxy groups, a curing accelerator that promotes a curing reaction between the base agent and the curing agent, a flame retardant, and a neutron absorbing material; The base material is hydrogenated bisphenol A diglycidyl ether, the curing agent is two or more selected from the group consisting of 4-alkyl endomethylene tetrahydrophthalic anhydride, 7-alkyl endomethylene tetrahydrophthalic anhydride, and endomethylene alkyl tetrahydrophthalic anhydride; The hardening accelerator is a neutron shielding material that is a compound that is solid or semi-solid at room temperature and has a melting point of 30° C. or higher and 45° C. or lower.
2. The neutron shielding material according to claim 1, A neutron shielding material in which the alkyl group of the curing agent is a methyl group, an ethyl group, or a propyl group.
3. The neutron shielding material according to claim 1, A neutron shielding material in which the amount of the curing agent is 50 parts by mass or more and 75 parts by mass or less per 100 parts by mass of the base material.
4. The neutron shielding material according to claim 1, The curing accelerator is a neutron shielding material selected from the group consisting of 2-ethyl-4-methylimidazole, 1-benzyl-2-phenylimidazole, 1,2-dimethylimidazole, and 1-cyanoethyl-2-ethyl-4-methylimidazole.
5. The neutron shielding material according to claim 1, A neutron shielding material, wherein the amount of the curing accelerator is 0.1 parts by mass or more and 4 parts by mass or less per 100 parts by mass of the base material.
6. The neutron shielding material according to claim 1, The neutron absorbing material is one or more selected from the group consisting of boron carbide and boron nitride.
7. The neutron shielding material according to claim 1, The flame retardant is a neutron shielding material that is aluminum hydroxide.
8. The neutron shielding material according to claim 7, A neutron shielding material in which the blending amount of the flame retardant is 150 parts by mass or more and 220 parts by mass or less per 100 parts by mass of the base material.
9. The neutron shielding material according to claim 1, A neutron shielding material, wherein the glass transition temperature of the epoxy resin is 165°C or higher and 180°C or lower.
10. A method for producing a neutron shielding material containing an epoxy resin as a main component, comprising the steps of: The neutron shielding material is composed of a cured product of a resin composition including a base agent including a compound having two epoxy groups in a molecule, a curing agent that causes ring-opening polymerization of the epoxy groups, a curing accelerator that promotes a curing reaction between the base agent and the curing agent, a flame retardant, and a neutron absorbing material; The base material is hydrogenated bisphenol A diglycidyl ether, the curing agent is two or more selected from the group consisting of 4-alkyl endomethylene tetrahydrophthalic anhydride, 7-alkyl endomethylene tetrahydrophthalic anhydride, and endomethylene alkyl tetrahydrophthalic anhydride; The curing accelerator is a compound that is solid or semi-solid at room temperature and has a melting point of 30° C. or higher and 45° C. or lower, The curing accelerator is heated to melt at an atmospheric temperature of 45° C. or more and 55° C. or less, A raw material liquid is prepared by mixing the base agent, the curing agent, the curing accelerator, the flame retardant, and the neutron absorbing material; The method for producing a neutron shielding material comprises thermally curing the raw material liquid at an atmospheric temperature of room temperature or higher and 55° C. or lower to obtain the cured product.
11. A method for producing the neutron shielding material according to claim 10, A method for producing a neutron shielding material, wherein the alkyl group of the curing agent is a methyl group, an ethyl group, or a propyl group.
12. The neutron shielding material according to claim 10, A method for producing a neutron shielding material, wherein the amount of the curing agent is 50 parts by mass or more and 75 parts by mass or less per 100 parts by mass of the base material.
13. A method for producing the neutron shielding material according to claim 1, The method for producing a neutron shielding material, wherein the hardening accelerator is 2-ethyl-4-methylimidazole, 1-benzyl-2-phenylimidazole, 1,2-dimethylimidazole, or 1-cyanoethyl-2-ethyl-4-methylimidazole.
14. A spent fuel assembly storage vessel for storing spent fuel assemblies, comprising: The spent fuel assembly storage container comprises an outer container, an inner container disposed inside the outer container, a basket disposed inside the inner container and storing spent fuel assemblies, and a neutron shielding material disposed between the outer container and the inner container, The neutron shielding material is composed of a cured product of a resin composition including a base agent including a compound having two epoxy groups in a molecule, a curing agent that causes ring-opening polymerization of the epoxy groups, a curing accelerator that promotes a curing reaction between the base agent and the curing agent, a flame retardant, and a neutron absorbing material; The base material is hydrogenated bisphenol A diglycidyl ether, the curing agent is two or more selected from the group consisting of 4-alkyl endomethylene tetrahydrophthalic anhydride, 7-alkyl endomethylene tetrahydrophthalic anhydride, and endomethylene alkyl tetrahydrophthalic anhydride; The hardening accelerator is a compound that is solid or semi-solid at room temperature and has a melting point of 30°C or higher and 45°C or lower.
Citation Information
Patent Citations
Composition for neutron shielding material, shielding material and vessel
JP2003050295A
Neutron shielding material and used fuel storage container
JP2003167091A
Neutron shielding material, and spent fuel storage vessel
JP2004198281A
Neutron shielding material and spent fuel storage cask
JP2007033059A
Manufacturing method of neutron shielding material, storage container, and neutron shielding agent
JP2021050972A